A POEM USING METAPHOR - Karjawbaev Orazali Esbosinuli; Toleubayeva A. O. (Web of Journals Publishing, 2024)
Adjectives characterize nouns and are frequently used in metaphors to further enhance the metaphor. The adjective is very likely to have the same meaning as the noun when the noun is metaphorical. In order to refer back to the original subject, it is also possible to utilize the adjective in opposition to the metaphor. A typical noun can also be described metaphorically in adjectives, which adds interest.
Keywords: Metaphor, theory of metaphor, political language, literary language, and comparison language metaphor, figurative metaphor, individual genuine metaphor.